Value chain analysis of fish in Meghalaya with special reference to East Khasi Hills District - Sumithra S.; Ram Singh (Umiam ; CPGS-AS, CAU, 2021)
In North East India, Assam contributes the most to fish production, followed by Tripura, Manipur and Meghalaya. In Meghalaya, the fishermen population was 16,567 out of 33, 66,710 (total population). Fish production and yearly fish consumption of Meghalaya during 2019-20 were 0.14 lakh MT and 10.98 (per capita/kg) respectively. Keeping the above facts in view, the research was conducted to analyze the value chain of fish in Meghalaya with special reference to East Khasi Hills district with the following objectives. 1) To map the actors involved in the value chain of fish business. 2) To estimate the compliance cost incurred by each of the value chain actors in the marketing of fish. Under Meghalaya, East Khasi Hills district was selected as it contributes more production. From this district, two blocks, viz., Mawphlang and Shella Bholaganj, were selected purposively. Primary data was collected from 30 fish farmers from the two villages in each block and 33 marketing agents from the Bara bazaar (kalewduh) and Sohra bazaar (lew sohra) were selected to study the actors involved in the value chain of fish. To achieve the above objectives, the producer$1 (Bs share in consumer$1 (Bs rupee, Acharya$1 (Bs modified marketing efficiency method, marketing cost, margin and price spread were used. Five value chains for fish were identified in the study area. The value chain, from fish farmer to consumer passes through a number of intermediaries: wholesalers, retailers, local traders, and a large volume of fish (54.32%) moving through the value chain-4 (Farmer-Wholesaler-Retailer Consumer).The study revealed that the value chain-1 (Farmer-Consumer) was the most efficient chain in which the farmers received the highest share of the consumer$1 (Bs rupee, followed by value chain-2 (94.14%) (Farmer-Fishery Department-Consumer). The marketing cost (42.69 per kg) and margin (51.30 per kg) were observed to be highest in value chain-5 (Farmer cum processor-Local Trader cum Retailer-Consumer). Additionally, net profit was found to be highest in value-added fish than compared to fresh ones. Therefore, value addition should be encouraged among fish farmers. s
Keywords: Fish -- Market analysis. -- Meghalaya; Fish -- Value addition -- Meghalaya